Differences in the Decomposition Time of Brain and Lower Gastrointestinal Tract in Male Wistar Rats (Rattus Norvegicus) in Lowland and Highland Soil - Abdul Hakim Nitiprodjo; Brilliant Chandra Arthamevia Suwanto; Norina Agatri; Muhammad Fadhol Romdhoni (Universitas Muhammadiyah Purwokerto, 2026)
Information in society, each person's body that is found can vary in condition, whether it is still fresh or has already rotted. Forensic science is needed to assist the investigative process, including determining the estimated time of death and the suspected cause of death. Thanatology is a branch of forensic science that studies the bodily changes that occur after death and provides definitive evidence of death. Decomposition of tissue is one of the sure signs of death caused by microorganisms both in the body and the environment. The objective of this research was to analyze the difference in decomposition time between the brain and the lower gastrointestinal tract in male Wistar rats buried in lowland soil and highland soil. This research is an experimental study with a repeated measures design. There are two treatment groups, each consisting of six male Wistar rats. Each group was euthanized using chloroform inhalation. The six rats in one group were buried in lowland soil, and the six in the other group were buried in highland soil. The brain and lower gastrointestinal tract organs were dissected. The Mann-Whitney test yielded p = 0.011, indicating significant differences in decomposition time between lowland and highland soil. Additionally, the decomposition time of the brain and lower gastrointestinal tract also showed significant differences, with p = 0.001. There are differences in the decomposition time between lowland and highland soils due to the distinct characteristics of these terrains. The lower gastrointestinal tract decomposes faster than the brain due to a higher population of bacteria in the gastrointestinal tract, which aids in the digestion process.